Water Contents and Monoglycerides as Development Role of Biodiesel Standard in Indonesia for B30 Implementation - Hermawan Febriansyah; Ary Budi Mulyono; Nibras Fitrah Yayienda; Febrian Isharyadi (IAES Indonesia Section, 2020)
Since 2016, Indonesia has implemented a policy of mixing biodiesel into diesel oil by 20 percents, also known as B20, based on regulation of the Minister of Energy and Mineral Resources number 12/2015. B20 is applied to all sectors that use diesel oil. In 2020, Indonesia continues to implement B30. Indonesia is the first nation in the world to implement B30, so Indonesia need biodiesel standard, especially biodiesel based from palm oil. This study is to present development standard of biodiesel in Indonesia. This study based on literature studies, discussion and biodiesel test sampling. The discussion is established by forum group discussion that consisting of government, industries and laboratories, and also by surveys to producers to take the biodiesel sample. This study result that the development of biodiesel standard in Indonesia is done by both road test and laboratory test. Monoglyceride and water content are the main concern of the validation of the biodiesel standard to implement B30 in Indonesia.